#1**+2 **

1. remember cos^2 + sin^2 = 1

sin^2 = 1- cos^2

sin = sqrt (15/16) (we are only concerned about the POSITIVE root in the 1st quadrant)

tan = sin/cos sqrt(15/16) / 1/4 = 4 sqrt(15/16) = 3.873

2. sin (theta - pi/2) results in shifting the sin wave pi/2 to the right which is an inverted cos wave

so sin (theta-pi/2) is - cos(theta) = - .54

ElectricPavlov
Feb 19, 2018

#1**+2 **

Best Answer

1. remember cos^2 + sin^2 = 1

sin^2 = 1- cos^2

sin = sqrt (15/16) (we are only concerned about the POSITIVE root in the 1st quadrant)

tan = sin/cos sqrt(15/16) / 1/4 = 4 sqrt(15/16) = 3.873

2. sin (theta - pi/2) results in shifting the sin wave pi/2 to the right which is an inverted cos wave

so sin (theta-pi/2) is - cos(theta) = - .54

ElectricPavlov
Feb 19, 2018